2002
DOI: 10.1079/bjn2002692
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and breast-feeding

Abstract: The objective of the present review is to discuss Se nutrition during breast-feeding, encompassing environmental and maternal constitutional factors affecting breast-milk-Se metabolism and secretion. A literature search of Medline and Webofscience was used to retrieve and select papers dealing with Se and breast milk. Although Se in natural foods occurs only in organic form, breast milk responds to organic and inorganic Se in supplements. Inorganic Se (selenite, selenate), which is largely used in maternal sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 145 publications
(138 reference statements)
8
72
2
2
Order By: Relevance
“…In human milk, worldwide Se values range between 13 and 33 mg/l and variations in levels are mainly due to fluctuations in the Se intake via food (Dumont et al, 2006). A decline of the Se secretion into the human milk also occurs during lactation, especially after the protein-rich colostrum is delivered (Dorea, 2002). Information on Se in marine mammals is limited, but the same dynamics of Se during lactation was shown in pigs (Kim and Mahan, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human milk, worldwide Se values range between 13 and 33 mg/l and variations in levels are mainly due to fluctuations in the Se intake via food (Dumont et al, 2006). A decline of the Se secretion into the human milk also occurs during lactation, especially after the protein-rich colostrum is delivered (Dorea, 2002). Information on Se in marine mammals is limited, but the same dynamics of Se during lactation was shown in pigs (Kim and Mahan, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It functions through selenoproteins such as glutathione peroxidase (Dorea, 2002), and protects animals from the toxicity of both inorganic Hg and MeHg (Khan and Wang, 2009). In higher-trophic marine animals, demethylation processes of MeHg are known to occur in the liver with a subsequent formation of HgSe granules (tiemannite), explaining the 1:1 M ratio of Se and Hg observed in these animals (Cuvin-Aralar and Furness, 1991; Koeman et al, 1973;Nigro and Leonzio, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…57, No. 6, 2011 SELENOMETHIONINE ABSORPTION IN DUODENUM OF ETHANOL-EXPOSED RAT OFFSRPING 709 their intestinal development; moreover, our research group has found that Se or Se plus folic acid supplementation during gestation and lactation could prevent liver oxidative damage in the pups, thus improving their development and health [10,11].At present, a limited number of studies have explored Se uptake in offspring rats [16] or infants [17,18], and there are no reports concerning this in ethanol-exposed pups. In this context, Anan et al (2009) [19] found that suckling pups mainly obtained Se presenting in breast-milk in organic form as Se-Met.…”
mentioning
confidence: 99%
“…At present, a limited number of studies have explored Se uptake in offspring rats [16] or infants [17,18], and there are no reports concerning this in ethanol-exposed pups. In this context, Anan et al (2009) [19] found that suckling pups mainly obtained Se presenting in breast-milk in organic form as Se-Met.…”
mentioning
confidence: 99%
“…Selenium concentrations in the soil vary in different regions, and the levels in pastures, animals, and human milk follow these regional variations [10]. The major species of selenium in plant sources are selenate (translocated directly from the soil), selenomethionine (SeMet), small amounts of selenocysteine (SeCys) and different seleno-containing proteins [9].…”
Section: Introductionmentioning
confidence: 99%